Epigenetic clocks as mediators of health behaviors and mortality in middle-aged and older adults - Xing-Ling Chen; Qiang-Qiang Zhao; Sheng-Rong Lin; Xing-Ling He; Xiao-Jiao Zhang; Si-Jing Li; Zi-Ru Li; Jia-Hui Chen; Hua Zhang; Xiao-Fang Li; Yue-Hui Zhou; Hui-Li Liao; et al. (The Journal of Nutrition, Health and Aging, 2025)
Background: The impact of healthy lifestyles on epigenetic age acceleration (EAA) and mortality in middle-aged/ senior populations remains unclear. This study investigates associations between lifestyle factors, EAA biomarkers, and mortality risk. Method: The 2532 adults of 50 years or older that registered in NHANES between 1999–2002.This study evaluated compares first- to third-generation epigenetic clocks (HannumAge, HorvathAge, PhenoAge, GrimAge2, DunedinPoAm) in predicting mortality risk associations between five lifestyle domains (diet, abdominal adiposity, physical activity, smoking, alcohol) and EAA were analyzed via multivariable regression, with mediation models testing EAA’s role in lifestyle-mortality relationships. Results: Survival curves results identified DunedinPoAm, GrimAge2AA, and PhenoAgeAA as robust biomarkers of accelerated biological aging, independent of chronological age. In multivariable linear regression models, full adherence to healthy behaviors reduced GrimAge2AA by β = −5.55 years, PhenoAgeAA by β = −2.64 years, and DunedinPoAm by β = −0.06 SD, with smoking cessation demonstrating the strongest GrimAge2AA attenuation (10.17 years). Stratified analyses revealed pronounced benefits: cancer patients adhering to healthy diets (β = −0.04 SD, P for interaction = 0.01) and hypertensive individuals reducing smoking (β = −0.05 SD, P for interaction = 0.04) showed significant EAA mitigation. The sensitivity analysis is consistent with the original results. Mediation analyses indicated GrimAge2AA accounted for 63.58% of lifestyle-survival associations, DunedinPoAm (44.63%) and PhenoAgeAA (28.45%). Conclusions: These findings suggest that comprehensive adherence to healthy lifestyle behaviors is associated with reduced epigenetic aging, supporting their potential utility as targets for mortality risk mitigation. And emphasize the utility of epigenetic clocks in precision gerontology.